Penerapan Metode Analytical Hierarchy Process Dalam Penentuan Prioritas Penanganan Jalan - Firdasari Firdasari; Iqbal Iqbal (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Maintenance of disaster evacuation routes is a priority in the field of disaster management to anticipate victims and losses. Supporting factors such as stable road conditions, the presence of security, relatively short distances and roadworthiness are criteria used as conditions for evacuation routes so that road handling needs to be maximized to function optimally. Decision making on road handling for evacuation routes in Langsa City must use a method so that alternative priorities from the disaster evacuation route can be identified. Analytical Hierarchy Process (AHP) method is one of the decision-making methods that has been widely used in determining the priority of road handling. The purpose of this study is to apply the AHP method as a decision making tool in determining the priority of road sections for evacuation routes for road handling in Langsa City. The stages of the method in this study were carried out by selecting criteria and alternatives that became the basis in determining road handling. The results obtained from this study were priority handling for flood evacuation routes with a weight of 46%, evacuation routes for natural disasters due to tidal waves 27% and other natural disasters by 9%. The results of this study are expected to assist local governments in making policies regarding the priority of handling roads that become disaster evacuation routes